Evaluation of Various Brands of Moisture Meters in Gypsum and Wood Substrates at a Range of Moisture Contents - Abel Crean (Civil Engineering Journal, 2017)
Determining correct moisture content of wetted building materials and analysis of corresponding locations, orientations, and patterns is of imminent value to Forensic Engineers and building scientists. As many building damages relate to insurance claims and construction defect/ subrogation lawsuits, legal challenges to the accuracy of measured moisture content have arisen. The objective of this study was to independently establish the level of precision of common moisture meters used to quantify and measure moisture content in building components. The study tested four different brand moisture meters in gypsum and wood substrates at normal, high, and saturated moisture contents. The results were compared against laboratory obtained moisture content to assess the accuracy of each meter in the substrate and at which moisture content range.The study wetted wood and gypsum specimens to moderate and saturated conditions and measured the resulting moisture content with the four different brands of meters. Control wood and gypsum specimens were not exposed to water and their moisture content was measured as is. All of the wood and gypsum specimens were subsequently sent to a laboratory and moisture content was calculated by the oven-dry method. The moisture content results measured by moisture meters were compared against the laboratory obtained data. Data was averaged and plotted with moisture content of various specimens and visually analysed to determine which meters deviated from the laboratory data and at which moisture contents. Data was also numerically analysed and graphed to quantify meter moisture content accuracy as compared to laboratory obtained moisture content.Moisture meters should be used within the manufacturer specified range of moisture content and price may not be the best indicator of moisture meter accuracy.  At low ranges of moisture content in wood and gypsum, all meters exhibited relatively small deviation from laboratory calculated values, while moderate and saturated conditions presented larger variations from laboratory moisture content. Composite materials such as gypsum may be difficult to establish moisture content, as different materials such as the gypsum core and paper facing absorb and distribute moisture differently. All meters were successful in detecting wet conditions, but exhibited a lack of precision in determining exact values in moderate and saturated conditions. In this regard, meters may be improved as the industry demands not only detecting wet conditions but determining precise values at a full range of moisture contents. Future studies may be limited to monolithic materials as oven dry method returns an average value of the respective paper and gypsum components in gypsum board specimens, and thus contained an inherent margin of error.